Stride length and stride frequency in three stages of preparation of high level sprinters - Paruzel, M.; Iskra, J.; Walaszczyk, A. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Results in sprint events (100-200 m run) depents on both stride length and stride frequency [1,2,3]. Previous works showed, that strid length and frequency depents on sex, body hight, sprint technique, level of motor preparation and preiod of training [1, 2, 3, 4]. The aim of this study was to find differences in both stride parameters in three periods of traning: general (in winter), special (in spring) and competition (in summer). Methods Nine best Polsih sprinters (100 m time, 10,25 (0,08s) s; body hight, 1,80 (0,08m), body weight, 74,1 (7,5kg) participated in this study. In three periods of preparation (Dec, Apr, Jul) they ran 60 m sprint from scratch start. Run time was measured by photocells. All runs was filmed by video camera. The stride length was estimated from numbers of strides and stride frequency was calculated from formula: number of strides / run time. Analysis of variance (ANOVA) was used to identify differences across stride length and frequency. Where ANOVA revealed significant at p 0,05, a post-hoc Tukey test was performed. Values in the text are reported as mean (standard deviation). Results There is statistically significantly differentes between stride frequency (F =6,09, p 01) and running velocity (F = 28,90, p 01) in three periods of training. The stride length was constants from winter to summer (F = 1,03) (table 1). Running velocity of sprinters depends on stride frequency (specially in winter and summer) and stride length (table 2). Discussion/Conclusions In all sprint training periods we must concentrated on development both stride frequency and stride length [1]. In competition periods (indoor and outdoor) speed frequency determines efficiency of sprint training. In April (special preparation period) sprinters concentrated on development of stride length.